- #1

- 42

- 1

## Homework Statement

If y' = 6x(x

^{2}+2)

^{2}and y = 25 when x = 1, what is the value of y when x = -1?

## Homework Equations

N/A3. The Attempt at a Solution [/B]

∫6x(x

^{2}+2)

^{2}dx = 2x(x

^{2}+2)

^{3}

(1

^{2}+ 3)

^{3}+ 2(1) + c = 25

1 + 2 = 3 and 2(1) = 2 and 3

^{3}= 27, so 27*2 + c = 25 so 54 + c = 25, therefore c = 25-54 = -29

Now substitute x = -1

(-1) squared is 1 and 2(-1) = -2, so 27*-2 = -54, so -54 - 29 = y = -83

WileyPlus tells me it's wrong.

What is wrong with this?